Designing a wholly online, multidisciplinary Master of Cancer Sciences degree - Julia Lai-Kwon; Sathana Dushyanthen; David Seignior; Michelle Barrett; Femke Buisman-Pijlman; Andrew Buntine; Robyn Woodward-Kron; Grant McArthur; David L Kok (BMC Medical Education, 2023)
Abstract Background Improving oncology-specific knowledge and skills of healthcare professionals is critical for improving the outcomes of people with cancer. Many current postgraduate education offerings may be inaccessible to busy professionals, contain minimal consumer input or do not focus on the multidisciplinary nature of cancer care. In response to these needs, a Master of Cancer Sciences degree was developed. Our aim is to describe the development of the Master of Cancer Sciences. Methods We describe the development of the Master of Cancer Sciences, including its theoretical and its pedagogical underpinnings. Results Our approach to curriculum design was guided by Kern’s Six-Step Approach to Medical Curriculum and underpinned by the Seven Principles of Online Learning. These approaches were further underpinned by the Cognitive Theory of Multimedia Learning which informed our approach to audio and visual information design. The pedagogy is interactive, experiential, interprofessional and importantly, includes consumers as educators. In practice, learning activities include peer feedback, multidisciplinary team meeting simulations, group work and clinical role plays. The online environment was visually shaped through infographics, high-quality educational videos and gamification. Conclusion We have designed a Master of Cancer Sciences that is one of the first wholly online, cancer-specific Masters’ programs. Its industry-led curriculum using evidence-based pedagogical choices utilises a range of novel digital formats and integrates the consumer perspective to provide a holistic overview of the field. Quantitative and qualitative evaluation of learning outcomes is ongoing.